Postgraduate education through university-industry link : The young engineers training programme - Nazir, Ramli; Mohd. Ghazali, Mohd. Zulkifli (1997)
In view of potential shortage of skilled engineers in the next century, the Malaysian government has taken a drastic turn to overcome this problem. In bringing it into fruition, the Malaysian government has already insist that a Malaysian-led joint venture companies which have secured major government projects, to provide training to the freshly graduated engineers as parts of its obligations in their contract agreement. This paper presents the experience of Universiti Teknologi Malaysia, (UTM) in setting up the special program through University-Industrial Link concept with the Linkedua Bhd which is a wholly own subsidiary co.mpany of United Engineers M~laysia Bhd. (UEM). The program is called "Young Engineers Training Programme" (YETP). Through this programme a freshly graduate Engineers were practically trained at site by Shimizu Corporation, the main contractor for the Malaysian-Singapore Second Crossing (MSSC) project. Apart from that, the trainees need to attend classroom lectures provided by UTM academic staff at site located at Kampung Ladang, Gelang Patah, Johor. The program was designed in such a way that it will reward the trainee with Post Graduate Diploma in Construction Management after all the requirement were met to the satisfaction of parties involved in the training program.